2015
DOI: 10.1111/jfr3.12177
|View full text |Cite
|
Sign up to set email alerts
|

Flood forecasting on the Tocantins River using ensemble rainfall forecasts and real‐time satellite rainfall estimates

Abstract: The Tocantins River, located at the northern region of Brazil with over 300 000 km2 of drainage area, is an important water body in terms of hydropower production. The occurrence of floods along the Tocantins River is a relatively frequent event that affects hydropower plant operations and several cities and their inhabitants. Motivated by recent flooding issues, a hydrological forecasting system was developed in order to assist the decision making of dam operation for flood control. The model uses merged rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 25 publications
0
37
0
3
Order By: Relevance
“…The choice of MGB for this study was motivated by several past applications in South America (Allasia et al, 2006), which encompassed rapid response (e.g., Collischonn et 15 al., 2005, Siqueira et al, 2016a to markedly seasonal and often slow response basins (e.g., Bravo et al, 2012;Paiva et al, 2013;Fan et al, 2016;Pontes et al, 2017). In its most recent version, basins are divided into unit-catchments (Paiva et al, 2011;Pontes et al, 2017), each one containing a single river reach with associated floodplain and hydrological vertical water Surface runoff is produced using the variable contribution area concept following the Arno model (Todini, 1996), while groundwater and subsurface flows are computed, respectively, with linear and nonlinear functions according to water availability in the soil layer.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of MGB for this study was motivated by several past applications in South America (Allasia et al, 2006), which encompassed rapid response (e.g., Collischonn et 15 al., 2005, Siqueira et al, 2016a to markedly seasonal and often slow response basins (e.g., Bravo et al, 2012;Paiva et al, 2013;Fan et al, 2016;Pontes et al, 2017). In its most recent version, basins are divided into unit-catchments (Paiva et al, 2011;Pontes et al, 2017), each one containing a single river reach with associated floodplain and hydrological vertical water Surface runoff is produced using the variable contribution area concept following the Arno model (Todini, 1996), while groundwater and subsurface flows are computed, respectively, with linear and nonlinear functions according to water availability in the soil layer.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Herein, we used the 400-m resolution HRU merged product (soil + land use) for South America (Fan et al, 2015), which is available at https://www.ufrgs.br/lsh. Basically, the soil map is a combination of the Brazilian database RADAMBrasil and the FAO Digitized Soil Map of the World and Derived Soil Properties, the latter included to account for areas lying outside Brazil.…”
Section: Land Use and Soil Data 20mentioning
confidence: 99%
“…The MGB-IPH model has an empirical data assimilation method coupled to updated streamflow by using routing module by Muskingum Cunge (PAZ et al, 2007;COLLISCHONN et al, 2005;COLLISCHONN et al, 2007b;TUCCI et al, 2006). The usefulness of this empirical model was demonstrated for reservoir inflow predictions based on quantitative precipitation forecast (COLLISCHONN et al, 2005;COLLISCHONN et al, 2007b) and flood forecasting using ensemble rainfall forecasts (FAN et al, 2014;FAN et al, 2016). A complete description of the empirical assimilation methodology can be found in the above mentioned articles.…”
Section: Methodology Distributed Mgb-iph Hydrological Modelmentioning
confidence: 99%
“…Research presented by Paz et al (2007), Collischonn et al (2005), Collischonn et al (2007b and Fan et al (2014) showed an empirical method of data assimilation for flood forecasting analyses in operational systems of inflows to the reservoirs. However, those techniques only allow assimilating the streamflow in rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that use the EPS technique for probabilistic streamflow forecasting are relatively new in Brazil. Fan, Schwanenberg, Collischonn, and Weerts (); Fan et al (, ) assessed the performances of three‐month seasonal forecasts in the upper São Francisco, Tocantins and Doce River basins in terms of their ability to predict reservoir inflow for management purposes using different EPS numerical models. In terms of short‐term flood forecasts, Siqueira, Collischonn, Fan, and Chou () and Casagrande, Tomasella, dos Santos Alvalá, Bottino, and Caram () tested the feasibility of the regional Eta model EPS in the Taquari Antas and Itajaí‐Açu basins, respectively, and concluded that the flood forecasts can be improved by using the EPS technique, mainly in terms of the lead time.…”
Section: Introductionmentioning
confidence: 99%